WAYS OF STRUCTURAL AND SEMANTIC FEATURES, SPEECH CONSTRUCTIONS IN SPEAKING AND DIALOGICAL SPEECH OF NATIONAL GROUP STUDENTS - S. ZH. ATAVULLAEVA (International Journal of Innovations in Engineering Research and Technology, 2021)
The article gives structural and semantic features of speech units that are used in teaching Russian grammar to first-year students for whom the Russian language is non-native. The problems of the correct selection of speech units for constructing dialogic speech are also considered.